Obstacles Of Consumer Dispute Settlement Agency In Resolution Of E-Commerce Disputes Between Consumers With Business Players - Herniati; Watkat, Fransiscus F.X (PT. Anagata Sembagi Education, 2025)
International recognition of consumers as the weak party is proven in UN General Assembly resolution No.A/RES/39/248 of 1985. Guidelines for Consumer Protection of 1985. According to the Guidelines for Consumer Protection of 1985, consumers must have certain basic rights, regardless of where they live. where they are or what country they come from. In the event that a consumer experiences a loss in an electronic transaction, the consumer has the option of complaining about the problem to BPSK or filing a lawsuit in district court, but the problem is whether the regulatory apparatus resolves consumer disputes through BPSK in electronic transactions (e-commerce), whether there are obstacles to the implementation of consumer dispute resolution. electronic transactions in implementing applicable regulations. The methods used in this research are legal research and descriptive analysis methods, with a normative juridical approach, namely research explaining the implementation of e-commerce dispute resolution. Consumer disputes through BPSK can only be resolved by agreeing on the form and amount of compensation as well as certain actions and a written statement explaining that the business actor will not repeat actions that harm consumers. It is hoped that there will be additional articles that specifically regulate dispute resolution efforts using non-litigation channels through BPSK because consumer dispute resolution regulations very narrowly regulate the process of resolving electronic transaction (e-commerce) disputes.